(untitled) (South East Asia Journal of Public Health, 2019)
Depression is the leading cause of disability worldwide. However, it is under recognized and undertreated. Self-rated health is a one-item question that has been used for population health monitoring. It was aimed to examine the prospect of using ‘self-rated health’ (SRH) in identifying people with depression among adult community-based population in Bangladesh over a one-year period controlling for socio-demographic, chronic diseases and symptoms, physical disability, smoking, and life events. We examined data from 3455 participants aged 18 years and above who participated in the 2015 January and 2016 January Health and Socio-Economic Survey of Independent University, Bangladesh. Using multiple logistic regressions, depression at baseline was examined to predict self-rated health at one-year follow-up adjusting for socio-demographic variables, chronic diseases, risk behaviors, and life events. Respondents with depression at baseline had 35% higher odds of reporting poor SRH in the follow-up round compared to those with no depression (OR=1.35, 95% CI=1.03 1.78, P<0.03). SRH may be used by community health workers as a preliminary indicator to identify people who may have depression followed by further screening and management for depression. South East Asia Journal of Public Health Vol.8(1) 2018: 10-16